The value of DHR-enzyme-linked immunosorbent assay in the diagnosis of chronic granulomatous disease by detecting NADPH oxidase complex activity - Xiaohui, Wen; Shunying, Zhao; Xiaoyan, Zhang; Xiaolei, Tang; Yuelin, Shen; Jinrong, Liu; Huimin, Li; Hui, Liu; Haiming, Yang (Frontiers in Pediatrics, 2025)
BackgroundA rapid, easy, and accurate method for screening Chronic Granulomatous Disease (CGD) is crucial. This study aimed to propose and evaluate the effectiveness of the DHR-Enzyme-linked immunosorbent assay (DHR-ELISA) for assessing NADPH oxidase complex activity in the early screening of CGD.MethodsWe conducted a retrospective analysis of 72 children suspected of having CGD who underwent NADPH oxidase activity assessment and genetic testing at Beijing Children's Hospital between July 2015 and January 2022.ResultsOf the subjects, 57 were male and 15 were female, resulting in a male-to-female ratio of 3.8:1. The median age at onset was 6 months, and the median age at diagnosis was 15 months. Thirty-eight patients were diagnosed with CGD based on typical clinical manifestations and genetic testing, exhibiting symptoms such as left lymphadenopathy or calcification (65.8%), a large Calmette-Guérin scar (60.5%), a history of skin or other lymph node infections (52.6%), and specific pulmonary infections (23.7%). Thirty-one patients exhibited normal enzyme activity, whereas 41 showed reduced activity. The DHR-ELISA method demonstrated a specificity of 90% and a sensitivity ranging from 90.5% to 100% in detecting CGD.ConclusionThe DHR-ELISA is a rapid, easy, cost-effective, and efficient method for screening CGD, making it suitable for early diagnosis and potentially improving prognosis.